Influenza virus infections from 0 to 2 years of age: A birth cohort study - Tamara Teros-Jaakkola; Laura Toivonen; Linnea Schuez-Havupalo; Sinikka Karppinen; Ilkka Julkunen; Matti Waris; Ville Peltola (Elsevier Ltd, 2022)
Background/purpose: Influenza vaccine has been recommended in Finland since
2007 for all children of 6e35 months of age and in 2009 for those 6 months against pandemic
influenza. We investigated the incidence of influenza and vaccine effectiveness in a birth
cohort of children in 2008e2011.
Methods: We followed 923 children from birth to 2 years of age for respiratory tract infections.
A nasal swab sample for PCR for influenza A and B viruses was taken at the onset of acute respiratory
infections. Samples were collected either at the study clinic or at home by parents.
Vaccination data was retrieved from the health registries.
Results: Vaccination coverage of children aged 6e23 months was 22e47% against seasonal
influenza and 80% against the A(H1N1)pdm09 virus in the pandemic season 2009e2010. During
3 influenza seasons, 1607 nasal swab samples were collected. Influenza was confirmed in 56
(6.1%) of 923 children (16 A(H1N1), 14 A(H3N2), and 26 B viruses). The incidence of influenza
was 5.1% in 2008e2009, 2.7% in 2009e2010, and 5.0% in 2010e2011. Effectiveness of the adjuvanted
vaccine against the pandemic influenza A(H1N1)pdm09 was 97% (95% confidence interval,
76e100%). Three children with influenza were hospitalized.
Conclusion: The yearly incidence of seasonal influenza was 5% in this cohort of very young children
with variable influenza vaccine coverage. Adjuvanted vaccine against the pandemic influenza
was highly effective. Both seasonal and pandemic influenza cases were mostly nonsevere.